Long-term follow-up of rituximab in treatment of chronic graft-versus-host disease—single center experience - Klobuch, Sebastian; Weber, Daniela; Holler, Barbara; Edinger, Matthias; Herr, Wolfgang; Holler, Ernst; Wolff, Daniel (Annals of Hematology, 2019)
Rituximab was recently described also as first-line therapy of chronic graft-versus-host disease (cGvHD). We retrospectively analyzed the efficacy and safety of all patients receiving rituximab for treatment of cGvHD between 2005 and 2016 at the Regensburg University transplant center with a median follow-up after rituximab therapy of 2.8 years. Responses of 29 allogeneic stem cell-transplanted patients (median age 49) with previous failure of response to steroids including one patient after donor lymphocyte infusion were assessed. Three months after rituximab application, the overall response rate was 31% (7% complete (n = 2) and 24% partial remission (n = 7)). At 12 months, overall survival was 72% (n = 21) and failure-free survival was 24% (n = 7). We further analyzed associations of rituximab response with clinical characteristics showing a higher response rate in steroid-dependent cGvHD patients (89% of 9 responding compared to steroid refractory patients (11% responding)). However, this difference was not statistically significant. Seven patients (24%) (including four lethal infectious complications) developed serious infections requiring hospitalization within 1–9 months after rituximab therapy exclusively in patients failing to respond to rituximab. In conclusion, rituximab appears to be an effective treatment of cGvHD especially in steroid dependent patients, but identification of biomarker predicting response will be crucial to avoid long-term infectious morbidity and mortality in non-responders.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Allogeneic stem cell transplantation; Chronic graft-versus-host disease; Rituximab